Spices and gastrointestinal health benefits: a state-of-the-art - Pauline Raoul; Campagna Chiara; Gianferrari Elisa; Nicodemo Mirella; Pizzari Ginevra; Marco Cintoni; Emanuele Rinninella; Esmeralda Capristo; Maria Cristina Mele (Nutrimentum et Curae)
Spices represent the basis of traditional medicine through the Middle East to Eastern Mediterranean and Europe since antiquity. In Western countries, spices are frequently used to impart flavor, reduce the need for salt and fatty condiments, improve digestion, and enhance their antioxidant effects. Thus, their diet-health linkages have drawn the attention of consumers, the scientific community, and the food industry. Indeed, their bioactive components are of considerable significance, making spices promising components to be included in a personalized diet. Numerous studies have demonstrated that spices have potential antioxidant, antimicrobial, and gastro-protective properties, and the role diet plays in preventing and treating many illnesses has been dissected. This review presents an overviewof the most common spices highlighting their anti-inflammatory, prebiotic, and anti-tumoral properties. Human clinical trials, specifically randomized controlled trials, are necessary to describe and demonstrate their health benefits to define it as a functional food.